Medical Aid for Spain : The work of the Spanish Medical Aid Committee - Peacock, W. Arthur; Jeger, George (London : Spanish Medical Aid Committee)
1937-12-28 SP01-003-17 26 pages : illustrations ; 22 cm JD 10.P6 PPC 2074